Using the Eyberg Child Behaviour Inventory to investigate Pester Power. (March 2019) - Page, Bill; Sharp, Anne; Lockshin, Larry; Sorensen, Herb
Abstract: Much research focuses on the "power" side of "pester power", with the assumption being that all requests are unwanted. Focusing on children aged under approximately 14 years old, and using recordings of 89 shopping trips, this paper uses the Eyberg Child Behaviour Inventory (new to the marketing literature) to investigate the "pester" aspect further and finds that, by and large, most trips are conducted without extreme child behaviours being exhibited. A third of children exhibit whining, and the remainder of scale items have low incidence of occurrence. These behaviours are also not found to be related to product requests. Roughly eighty percent of children made a request, and a fifth of these requests were granted. Parents do overall exercise power as gatekeepers for the food their children eat and do appear to exercise this power in-store in addition to regulating their disruptive behaviour. Future research needs to consider the wider opportunities children have to influence their parents and their influence in other retail contexts outside grocery shopping.